STRATEGI PENGEMBANGAN NANOTEKNOLOGI DALAM RANGKA PENINGKATAN DAYA SAING INDUSTRI PERTANIAN NASIONAL DENGAN MENGGUNAKAN SWOT-ANP - Rochman, E, Nurul Taufiqu; Daryanto, Arief; Nuryartono, Nunung; Sa’id, Gumbira (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2010)
Nanotechnology is believed to give a significant added value to agricultural industry. Various applications of nanotechnology provide opportunities for improving the global competitiveness of agricultural industry. This study aims to assess nanotechnology development strategy at the national agricultural industry by using quantitative SWOT method and ANP in BOCR (benefit, opportunity, cost, risk) perspective. The results from these two approaches were then compared. There were four stages of research procedure that consists of 1) analyzing agricultural industries that apply nanotechnology using quantitative SWOT, 2) formulating nanotechnology development strategy in the TOWS matrix quantitatively, 3) determining strategy alternative for developing nanotechnology on agricultural industry with ANP in BOCR perspective and 4) assessing comparatively weight value of each strategy alternative using quantitative SWOT and ANP in BOCR perspective. Data was collected by conducting FGD (group discussion forum) for 20 participants and questionnaire to 10 experts in the field of food chemistry, agriculture, nanotechnology and policy. Results show that in formulation of nanotechnology development strategy on national agriculture industry, aspects of opportunities and positive impact are taken to account more than that risk and economic aspects. ANP results indicate that nanotechnology development on national agricultural industry is still in the early stage where strategy that leads to increased mastery of technology is payed more intention than the implementation of research result itself, socialization of nanotechnology safety and governance of policies. Strategy formulation done by ANP in BOCR perspective is slightly difference than that of done by quantitative SWOT method which uses only independent variables. The result of this study can be used as a reference for stake holders for strategic decision making in relation to improving competitiveness of national agricultural industry through the development of nanotechnology.